1996
DOI: 10.1063/1.115807
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient band-edge emission from InP quantum dots

Abstract: High quality InP quantum dots with diameters ranging from 25 to 45 Å, have been prepared; these quantum dots (QDs) show high quantum yields for band-edge photoluminescence (lowest energy HOMO-LUMO transition). The wavelength of the blue-shifted band-edge emission ranges from about 575 to 730 nm depending on QD size. The quantum yield for photoluminescence is 30% at 300 K and 60% at 10 K; the multiexponential decay of this emission exhibits lifetimes ranging from 5 to 50 ns. Deep red-shifted emission due to tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
109
0
3

Year Published

2001
2001
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 286 publications
(120 citation statements)
references
References 1 publication
8
109
0
3
Order By: Relevance
“…We describe efforts to enhance quantum-wire PL by photochemical etching with HF, which has proven successful for InP quantum dots. 1,2 We show that with InP quantum wires the method affords only photochemical wire thinning or photo-oxidation. The PL enhancements ultimately obtained are due to residual quantum-dot and quantum-rod domains left in the wires after photo-oxidation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We describe efforts to enhance quantum-wire PL by photochemical etching with HF, which has proven successful for InP quantum dots. 1,2 We show that with InP quantum wires the method affords only photochemical wire thinning or photo-oxidation. The PL enhancements ultimately obtained are due to residual quantum-dot and quantum-rod domains left in the wires after photo-oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Therefore, a detailed analysis of the band gaps and PL behavior exhibited by InP quantum wires is provided. We describe efforts to enhance quantum-wire PL by photochemical etching with HF, which has proven successful for InP quantum dots.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of PEG to the solution in which the nanoparticles were dispersed caused capping nanoparticles [33,34]. Surface passivation by polymer coating would be effective to prevent such a reduction of afterglow properties [19][20][21]. In this study, the addition of PEG increased the quantum yield, as shown in Figure 5.…”
Section: Resultsmentioning
confidence: 57%
“…Therefore, the florescence intensity and the quantum yield are decreased in the case of nanoparticles. There were many reports that passivation of fluorescent nanoparticles by polymers increased the fluorescence intensity [19][20][21]. Capping nanoparticles with PEG is also important for minimizing the nonspecific adsorption of proteins related to the immune system [25,26].…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation